PENYELENGGARAAN HYGIENE SANITASI PENGOLAHAN SALAK DI PT. AGRINA DESA PARSALAKAN KECAMATAN ANGKOLA BARAT KABUPATEN TAPANULI SELATAN TAHUN 2013 - Yuli Arisyah Siregar; Surya Dharma; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2013)
Operation Of Hygiene Sanitation Salak Processing At PT. Agrina Parsalakan Village West Angkola Subdistrict South Tapanuli District In 2013. Efforts to control dietary factors, people, places and equipment that may or may cause illness or health problems, it is necessary hygiene sanitation in any food processing in order to avoid contamination. Salak (Salacca edulis) is a plant which its stalk close by midrib leaves, prickly on midrib and stems leaves, fleshy white fruit, blackish brown hard seeds. The manufacturing process of all kinds of processed salak using white sugar/sakarosa. Application of hygiene sanitation on food processing can make a better quality food product. The purpose of this research was to determine the implementation hygiene sanitation on salak manufacturing and analysis of artificial sweetener which are produced by PT. Agrina Parsalakan Village, West Angkola Subdistrict, South Tapanuli District in 2013. The research was descriptive survey to see the implementation of hygiene sanitation and laboratory analysis for determine the presence of artificial sweetener on salak manufacturing. The samples taken from types of processed salak which are produced by PT. Agrina Parsalakan Village, West Angkola Subdistrict, South Tapanuli District. The results showed that the principles of hygiene sanitation on salak manufacturing which qualified is the selection of raw materials, storage of raw materials, food storage and food transport. Whereas the food processing and food serving are not eligible, this refers to Kepmenkes RI No. 942/Menkes/SK/VII/2003. There are no artificial sweeteners in processed salak on six samples tested in the laboratory. Health Department need to make a comprehensive counseling and supervision by the relevant agencies (Health Department) about the importance of hygiene sanitation on snack, and development to the producer about the use of sweetener in food. Keywords: Salak, Sanitation Hygiene, Artificial Sweeteners